2019
DOI: 10.7748/ns.2019.e11278
|View full text |Cite
|
Sign up to set email alerts
|

Assessing physical activity levels in people living with a stoma

Abstract: Background: Physical activity is important for physical and mental health although people with a stoma commonly experience a reduction in physical activity following their stoma formation. Aim:To assess whether adults with a stoma achieve the recommended amount of physical activity, and to identify any barriers and facilitators that may influence their participation.Method: Community-residing adults living with a urostomy, ileostomy and colostomy were recruited from six regional stoma support groups. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Thirty-seven percent of rectal cancer survivors with a stoma met or exceeded recommendations in a large US survey [30] and so did less than 20% of stoma patients in a small British survey of patients attending a support group [31]. Both numbers are markedly lower than the 51% meeting guideline recommendations in our sample.…”
Section: Discussioncontrasting
confidence: 62%
“…Thirty-seven percent of rectal cancer survivors with a stoma met or exceeded recommendations in a large US survey [30] and so did less than 20% of stoma patients in a small British survey of patients attending a support group [31]. Both numbers are markedly lower than the 51% meeting guideline recommendations in our sample.…”
Section: Discussioncontrasting
confidence: 62%
“…These HADS scores are within the normal range (0–7) for the HADS scoring criteria, and thus did not meet the clinical threshold for major depressive disorder [ 17 ]. Of the included studies, four used the PHQ-9 as a measure of depressive symptoms, however none reported raw PHQ-9 scores, merely rates of depressive symptoms within the study population [ 45 , 62 , 69 , 82 ]. Of the four included studies that used the BDI, all reported mean scores [ 25 , 42 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…An intervention that involves appropriate physical activity for rehabilitation for physical recovery is important after an illness or surgery. Providing exercise is secure during and after chemotherapy for cancer and leads to enhancements in physical functioning, fatigue, and quality of life [ 11 , 12 ]. So, individuals who have ostomies need specific care during the recovery and rehabilitation phases to improve their physical activity and maintain their physical well-being and quality of life [ 13 ].…”
Section: Introductionmentioning
confidence: 99%